Effects of Intercropping with Potato Onion on the Growth of Tomato and Rhizosphere Alkaline Phosphatase Genes Diversity - Wu, Xia; Wu, Fengzhi; Zhou, Xingang; Fu, Xuepeng; Tao, Yue; Xu, Weihui; Pan, Kai; Liu, Shouwei (Frontiers in Plant Science, 2016)
Background and aims: In China, excessive fertilization has resulted in phosphorus (P) accumulation in most greenhouse soils. Intercropping can improve the efficiency of nutrient utilization in crop production. In this study, pot experiments were performed to investigate the effects of intercropping with potato onion (Allium cepa L. var. aggregatum G. Don) on tomato (Solanum lycopersicum L.) seedlings growth and P uptake, the diversity of rhizosphere phosphobacteria and alkaline phosphatase (ALP) genes in phosphorus-rich soil. Methods: The experiment included three treatments, namely tomato monoculture (TM), potato onion monoculture (OM), and tomato/potato onion intercropping (TI-tomato intercropping and OI-potato onion intercropping). The growth and P uptake of tomato and potato onion seedlings were evaluated. The dilution plating method was used to determine the population of phosphate-solubilizing bacteria (PSB) and phosphate-mineralizing bacteria (PMB). The genomic DNAs of PSB and PMB in the rhizosphere of tomato and potato onions were extracted and purified, and then, with the primer set of 338f /518r, the PCR amplification of partial bacterial 16S rDNA sequence was performed and sequenced to determine the diversities of PSB and PMB. After extracting the total genomic DNAs from the rhizosphere, the copy numbers and diversities of ALP genes were investigated using real-time PCR and PCR-DGGE, respectively. Results: Intercropping with potato onion promoted the growth and P uptake of tomato seedlings, but inhibited those of potato onion. After 37 days of transplanting, compared to the rhizosphere of TM, the soil pH increased, while the electrolytic conductivity and Olsen P content decreased (p < 0.05) in the rhizosphere of TI. The populations and diversities of PSB, PMB, and ALP genes increased significantly in the rhizosphere of TI, compared to the rhizosphere of TM. Conclusion: The results indicated that intercropping with potato onion promoted the growth and P uptake of tomato in phosphorus-rich soil and affected the community structure and function of phosphobacteria in tomato rhizosphere. Intercropping with potato onion also improved soil quality by lowering levels of soil acidification and salinization.